THE INFLUENCE OF THE APPLICATION OF MANAGEMENT ACCOUNTING INFORMATION, METHODS OF MEASURING PERFORMANCE ON MANAGERIAL PERFORMANCE IN STATE SAVINGS BANKS - Abdurrohman, Abdurrohman; Gatot Hartoko; Atika Anggi Hafsara (SEAN Institute, 2022)
This study aims to determine how the influence of the application of management accounting information, and performance measurement methods on managerial performance. This research was conducted at Bank Tabungan Negara in Serang and Cilegon Regions by distributing questionnaires to the managerial level with 42 respondents. This research used descriptive analysis, multiple regression analysis, and classical assumption test consisting of normality test, test multicollinearity, heteroscedasticity test, and hypothesis testing were carried out by partial testing (t-test), simultaneous testing (f test) and determination (R2) using the SPSS test tool version 22. From the results of research conducted partially, management accounting information, performance measurement methods, on managerial performance at the State Savings Bank have a significant effect, then simultaneously obtained the results of the independent variable, namely management accounting information, performance measurement methods have a significant effect on the dependent variable, namely performance. managerial at the State Savings Bank from the results of the coefficient of determination (R2) shows that the independent variable influences 0.573 or 57.3%,